The Critical Role of Adipocytes in Leukemia - Romane Higos; Kevin Saitoski; Mathieu Hautefeuille; Geneviève Marcelin; Karine Clément; Nadine Varin-Blank; Christophe Breton; Simon Lecoutre; Mélanie Lambert (Biology, 2025)
The bone marrow microenvironment is a dynamic and complex niche that plays a central role in the development, progression, and therapeutic resistance of leukemia. Among the various stromal and immune cells that compose this microenvironment, adipocytes are increasingly recognized as active participants rather than passive bystanders. These cells contribute to leukemia pathophysiology by supplying leukemic cells with vital metabolic fuels such as free fatty acids and glutamine, which support cellular bioenergetics and biosynthesis. Furthermore, adipocytes secrete adipokines—including leptin, adiponectin, and others—that influence leukemic cell proliferation, apoptosis, and chemoresistance. Leukemic cells, in turn, are not merely recipients of these signals, but actively remodel the marrow niche to their advantage. They can suppress adipogenesis, inhibit the differentiation of mesenchymal stem cells into adipocytes, or reprogram existing adipocytes to adopt a tumor-supportive phenotype. These transformed adipocytes may enhance leukemic cell survival, dampen immune responses, and create a metabolic sanctuary that enables resistance to standard chemotherapies. This reciprocal and dynamic interaction between leukemic cells and adipocytes contributes significantly to minimal residual disease and relapse, posing a major challenge for durable remission. Recent advances in tissue engineering—such as organ-on-chip and 3D co-culture systems—offer promising platforms to recapitulate and study these leukemia–adipocyte interactions with high fidelity. These models facilitate mechanistic insights and provide a foundation for developing novel therapeutic strategies aimed at disrupting the metabolic and paracrine crosstalk within the leukemic niche. Targeting the adipocyte–leukemia axis represents a compelling and underexplored avenue for improving leukemia treatment by sensitizing malignant cells to existing therapies and overcoming the protective influence of the bone marrow microenvironment.